A Study of E-Commerce’s Business on the Retail Sector: Exploring the Impact of E-commerce on the Retail Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Introduction to e-commerce, influence of e-commerce on the globe today, impact of e-commerce on markets and retailers, retail sector, FDI policy, retailer impact on e-commerce company, and various markets and retailers in India were discussed in this paper. The thorough explanation of the title related topics was clearly presented in this chapter. We primarily focused on the study’s goal and hypothesis